2020
DOI: 10.1016/s1470-2045(19)30728-4
|View full text |Cite
|
Sign up to set email alerts
|

Cemiplimab in locally advanced cutaneous squamous cell carcinoma: results from an open-label, phase 2, single-arm trial

Abstract: DR recruited patients and collected the data. SL did the data analysis. All authors contributed to data interpretation, as well as critical review, revision, and approval of the report. Data sharingQualified researchers can request access to study documents (including the clinical study report, study protocol with any amendments, blank case report form, and statistical analysis plan) that support the methods and findings reported in this report. Individual anonymised participant data will be made available onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
435
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(464 citation statements)
references
References 28 publications
13
435
1
15
Order By: Relevance
“…The data from the Phase 2 study of 78 patients with locally advanced cSCC have just been published in January 2020 in Lancet Oncology 6 . The median duration of study follow‐up was 9.3 months (IQR 5.1‐15.7) at the time of data cutoff.…”
Section: Cemiplimab the New Promising Immune Checkpoint Inhibitormentioning
confidence: 99%
“…The data from the Phase 2 study of 78 patients with locally advanced cSCC have just been published in January 2020 in Lancet Oncology 6 . The median duration of study follow‐up was 9.3 months (IQR 5.1‐15.7) at the time of data cutoff.…”
Section: Cemiplimab the New Promising Immune Checkpoint Inhibitormentioning
confidence: 99%
“…The most common therapeutic regimens are chemotherapy and epidermal growth factor receptor (EGFR) inhibitors [1][2][3]. However, some studies have reported the low efficacy of cytotoxic chemotherapies (cisplatin, 5-fluorouracil (5-FU), bleomycin, and doxorubicin) and EGFR inhibitors [4,5]. Due to the fact that cutaneous SCC in the advanced stage has limited response to common therapies, investigations into systematic therapies with better response rates are crucial [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Four prospective phase II studies and one phase I study were identified. [3][4][5][6][7][8] The remaining records included one expanded-access programme, two retrospective analyses and 22 case reports or series. The number of patients per study ranged from one to 137.…”
mentioning
confidence: 99%
“…We identified results for cemiplimab (six records), pembrolizumab (19 records), nivolumab (nine records), combined ipilimumab with nivolumab (one record) and ipilimumab (one record). The ORR ranged from 36% to 55% 3,4 for pembrolizumab and from 44% to 49% [6][7][8] for cemiplimab ( Table 1). Severe adverse events were observed in 23-29Á5% of the patients treated with cemiplimab, but they were poorly reported for other agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation